Religion and social transformations in Cyprus : from the Cypriot basileis to the Hellenistic strategos - Papantoniou, Giorgos. (Mnemosyne, Supplements, 2012)
This monograph focuses on religion to explore how the socio-cultural infrastructure of Cyprus was affected by the transition from segmented administration by many Cypriot kings to the island-wide government by a foreign Ptolemaic correspondent. It approaches politico-religious ideological responses and structures of symbolism through the study of sacred landscapes, specific iconographic elements, and archaeological contexts and architecture, as well as through textual and epigraphic evidence. A fresh approach to the transition is put forward, connecting the island more emphatically with its longue durée. Moving beyond the field of Cypriot studies, this work also serves as a paradigm for the study of religion in relation to social power in other fields of classics and, in particular, for the enrolment of other areas of the Mediterranean into the political and cultural Hellenistic oikoumene.